Managerialism Against Clientelism. A Blocked Process of Political Change in Apulia (Southern Italy) - Galimberti, Deborah (PARTECIPAZIONE E CONFLITTO, 2022)
This article aims to explain the evolution of forms of political regulation for the allocation of resources and representation of interests in Southern Italy, at length qualified as clientelistic. It will show how managerial principles can be taken up in a context with a historical resistance to bureaucratic change as well as a political orientation which contests neoliberal beliefs. To this end, it analyses a sequence of political change in the Apulia region, while focusing on the political strategies and discourses concerning local development tools for entrepreneurs. It shows how the objective to increase the regional council’s institutional capacity to deliver public policies turned into a managerial drift. It is argued that the critique of clientelism, considered the main factor hindering the development of the South, led to the prioritisation of efficiency over representation of collective interests. The critique of clientelism corresponds to the mechanism through which managerialism has spread in a context of economic crisis.